Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel